Validation of a decision support tool for wastewater treatment selection. (15th December 2016) - Castillo, A.; Porro, J.; Garrido-Baserba, M.; Rosso, D.; Renzi, D.; Fatone, F.; Gómez, V.; Comas, J.; Poch, M.
Abstract: Wastewater treatment selection is a complex task usually addressed by applying separate tools for the correct assessment of multi-criteria evaluation. Novedar_EDSS integrates technical, environmental, economic and social assessment capabilities in one single platform. The aim of this work is to evaluate and demonstrate the capabilities of this environmental decision support system (EDSS). For that purpose, 4 case studies of real projects were selected to validate the results in the EDSS by comparing them with those from the study of alternatives performed by the decision makers. Moreover, 1 conceptual case study was applied to support the selection of the most properly strategy for plant retrofitting. Results have demonstrated that the EDSS provides key aspects when deciding the retrofitting process to apply and, when compared to real projects, it recommends analogue treatments as those applied in the projects, ranking them in the same order. Therefore, results in the validation process performed show that this tool provides a reliable basis to support decision makers to select properly treatment alternatives in wastewater treatment plant pre-design. Highlights: Validation of a decision support system for wastewater treatment is performed. 5 case studies are selected (4 real and 1 conceptual) for new plant and retrofitting. Results in the tool are compared with process flow diagrams in the real case studies. The tool recommends analogous treatments as those selected by decision-makers. Reliability of the tool in pre-design of wastewater treatment plants is demonstrated.